ANALYSIS OF TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION FACTORS IN IMPROVING EMPLOYEE PERFORMANCE AT THE LAMPUNG REGIONAL OFFICE OF THE NATIONAL LAND AGENCY (BPN) - Anggraini, Yuni; Alam, Iskandar Ali (Jurnal Riset Multidisiplin Edukasi, 2026)
This study was motivated by the continuing need to improve employee performance in supporting effective, efficient, timely, transparent, and accountable land administration services. Transformational leadership and work motivation are considered important factors that can encourage employees to perform their duties and responsibilities optimally. This study employed a quantitative approach using a survey method. The research data were collected through questionnaires distributed to employees of the Regional Office of the National Land Agency (BPN) of Lampung Province and were subsequently analyzed using regression analysis to examine both partial and simultaneous effects. The results showed that: (1) transformational leadership had a positive and significant effect on employee performance; (2) work motivation had a positive and significant effect on employee performance; (3) transformational leadership and work motivation simultaneously had a positive and significant effect on employee performance; and (4) transformational leadership was the variable that exerted the most dominant influence on employee performance compared with work motivation. These findings indicate that the better the implementation of transformational leadership and the higher the level of employee work motivation, the more optimal the resulting performance. Therefore, the Regional Office of the National Land Agency (BPN) of Lampung Province needs to strengthen the implementation of transformational leadership through exemplary behavior, inspiration, intellectual stimulation, and individualized consideration, while also enhancing work motivation through recognition and rewards, career development, education and training, and the creation of a conducive work environment. These efforts are expected to continuously improve employee performance and contribute to enhancing the quality of land administration services provided to the community.